v.7 - Mishra, Madhu S. (ed.) (Calcutta, 1991)
Development of rural sector plays a crucial role in the context of India's longterm economic development and growth objectives. The need for appropriate strategies for accelerating the pace of rural development activities is increasingly felt by planners, development administrators, researchers and the organisations involved in implementation of such activities. It is often realised that the existing information as well as knowledge base on the rural sector are inadequate for ensuring effectiveness in the above endeavour. Inview of the diversities and complexities involved in understanding the operation of different systems and sub-systems in the rural sector, the available literature on the subject seem to be meager and are widely scattered often lacking in time series data. This proves extremely inadequate for proper understanding of the rural sector and analysis of the emerging issues in solving problems of developmental efforts. From the perspective of the greater emphasis being given to the integrated rural development programme by the government and other organisations in the recent years, the effective planning and implementation, there is scope for enhancing our knowledge, information and data base on the rural sector though systematic research and studies in the areas of rural economy, ecology and society. Despite our experience of rural development programmes through our planning efforts, to-day the need for up-to-dating our knowledge and understanding of the rural sector thus seem to be greater than even before for ensuring the desired goals of developing rural India.
Keywords: Bibliography management rural development